MEMBONGKAR ISI PESAN DAN MEDIA DENGAN CONTENT ANALYSIS - Gusti Yasser Arafat (UIN Antasari Banjarmasin, 2019)
Content analysis in a quantitative research tradition is a method of communication science research and also for some of another social sciences branch. The quantitative content analysis is in the scope of positivistic paradigm that put its researcher as a neutral scientist who do not take a side and forbidden prohibited to product opinion. The researcher is only need to collect and then categorizing meaning of a content such as text, image, sign, and symbol. Content analysis is also able to test a hipotetic using deductive methode by series of statistic test. In communication sciences, this research methode model would powerful to answer how the media effect which impact to public and analyzing the people all at once. The difference between social construct in society and the recontructed reality by the media would being explained using this great methode. Content analysis is capable to measure the accuracy level of message producer and where it’s inclined.